Aplikasi Desain Generatif Pada Rangka Sepeda Dengan Menggunakan Perangkat Lunak Solidworks dan Matlab Simulink - Muhammad Ilham Baihaki; Carolus Bintoro (INOVTEK - SERI MESIN, 2021)
This research discusses the application of generative design on mountain bike frames using Solidworks and MATLAB Simulink software. The topic is taken from the problem of the inertial force that occurs in the structure of a mountain bike due to the dynamic forces that work. In the implementation, several things were carried out, namely the first to design the geometry of the mountain bike frame and determine the static load using solidworks software. Second, bicycle track modeling and dynamic load determination method using MATLAB simulink software. Third, numerical simulation on mountain bike frames with static and dynamic loads using solidworks. Thus, in this research a computational study was carried out using Solidworks and MATLAB simulink software. From the computational study, the results of different dynamic forces are obtained at each loading. At a maximum of mass of 90 kg the rider produces a static force of 1695,1 N and a dynamic force of 36,78 N. Under these loading conditions, a positive margin of safety is obtained so that the frame design of a mountain bike is declared safety.Keywords: Generative, Bike Frame, Solidworks, MATLAB simulink